MOTION GRAPHICS APPLICATIONS: EXPLORING CONCEPTUAL LOGO DESIGN IN GHANA - Ayim, Bertha; Adashei, Michael; Kushiator, George; Tetteh, Prince; Howard, Ebenezer (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
The development of motion graphics techniques in the 20th Century has transformed the discipline of the static graphics industry. Logo designing in Ghana almost lacks a conceptual framework, therefore, this paper explores the use of motion graphics as a conceptual framework for logo designing. Through studio practice and critical observation, the study revealed the difficulty of local designers within the informal sector in producing conceptual logos for clients. Using a simple random technique, fifty (50) designers were selected from the printing and advertising firms in the Kumasi metropolis where the participants were taken through conceptual logo designing. The study established that designers need great background knowledge of the clients and their competitors in order to come out with conceptual logos that can bring out hidden messages for viewers to understand. This can only be achieved through careful design planning and execution. The study therefore recommends that the effective designing of a conceptual logo should include the conglomeration of visuals and text.